COMPARISON OF THE PHYSICAL EXAMINATION SKILLS LEARNING PROCESS BEFORE AND DURING COVID-19 PANDEMIC BASED ON EXPERIENTIAL LEARNING THEORY: A MIXED-METHOD STUDY - Sastri, Ni Luh Putu Pranena; Hidayah, Rachmadya Nur; Widyandana, Widyandana (Universitas Gadjah Mada, 2023)
Background: COVID-19 pandemic has changed learning physical examination skills. Online learning physical examination skills are challenging because it needs standard practice facilities, and students need opportunities to practice. Physical examination skills are essential in clinical medical practice, but research before pandemic demonstrated students’ lack of skills acquisition. Evaluation is needed to determine the differences in the learning process before and during pandemic. This study aims to compare the learning physical examination skills process before and during COVID-19 pandemic and find recommendations for the future.Methods: This research was a mixed-method study with a convergent design. The samples are students and lecturers in the Faculty of Medicine Universitas Pendidikan Ganesha. Quantitative data was obtained from a developed questionnaire about students’ perception of the physical examination skills learning process, then analyzed descriptively and using the ANOVA test. Qualitative data was obtained by interview, then analyzed using thematic analysis.Results: There are significant differences in the learning process of face-to-face, online, and blended physical examination skills (p<0.05) but no difference between face-to-face and blended. Interview results have seven themes, four themes about difference in the learning process based on Kolb Experiential Learning Theory, other themes about preparation before learning, factors in the learning process, and recommendations.Conclusion: Differences in the physical examination skills learning process are in the skills demonstration, practice opportunities, feedback, and interactions. If learning physical examination skills is carried out face-to-face, online, or blended in the future, it will have different needs to be considered in the design and implementation.